Reproduction and viscera organ characteristics of MSTN and FGF5 dual-gene knockout sheep - Chen, Mingming; Zhao, Yue; Li, Yao; Chen, Tiantian; Zhou, Wendi; Zhang, Xiaosheng; Deng, Shoulong; Xu, Xueling; Wu, Sujun; Liu, Zhimei; Qi, Shiyu; Wang, Luyu; et al. (Frontiers in Veterinary Science, 2023)
Introduction Myostatin (MSTN) negatively regulates skeletal muscle development. However, its function in reproductive performance and visceral organs has not been thoroughly investigated. Previously, we prepared a MSTN and fibroblast growth factor 5 (FGF5) double-knockout sheep, which was a MSTN and FGF5 dual-gene biallelic homozygous (MF−/−) mutant. Methods To understand the role of MSTN and FGF5 in reproductive performance and visceral organs, this study evaluated the ejaculation amount, semen pH, sperm motility, sperm density, acrosome integrity, rate of teratosperm, and seminal plasma biochemical indicators in adult MF−/− rams. We also compared the overall morphology, head, head-neck junction, middle segment and the transection of middle segment of spermatozoa between wildtype (WT) and MF−/− rams. Results Our results showed that the seminal plasma biochemical indicators, sperm structure and all sperm indicators were normal, and the fertilization rate also has no significant difference between WT and MF−/− rams, indicating that the MF−/− mutation did not affect the reproductive performance of sheep. Additional analysis evaluated the histomorphology of the visceral organs, digestive system and reproductive system of MF+/− sheep, the F1 generation of MF−/−, at the age of 12 months. There was an increased spleen index, but no significant differences in the organ indexes of heart, liver, lung, kidney and stomach, and no obvious differences in the histomorphology of visceral organs, digestive system and reproductive system in MF+/− compared with WT sheep. No MF+/− sheep were observed to have any pathological features. Discussion In summary, the MSTN and FGF5 double-knockout did not affect reproductive performance, visceral organs and digestive system in sheep except for differences previously observed in muscle and fat. The current data provide a reference for further elucidating the application of MSTN and FGF5 double-knockout sheep.